Frequency and Visual Outcome of Choroidal Tubercles with Miliary Tuberculosis - Baig, Mirza Shafiq Ali; Masroor, Muhammad; Syed Muhammad Adnan, Jameel A. Burney, Farnaz Siddiqui , Mazhar-ul-Hassan, Sarfaraz Nawaz (Pakistan Journal of Ophthalmology, 2014)
Purpose: To determine the frequency and visual outcome of choroidal tubercles in diagnosed cases of Miliary Tuberculosis. Material and Methods: A prospective study was conducted at Department of Ophthalmology and institute of Chest Disease (OICD) Dow University Hospital (DUH), Dow International Medical College (DIMC) and Dow University Of Health Sciences (DUHS) Karachi, 24th April, 2010 to 23rd November, 2013. Two hundred and seventy two (272) diagnosed cases of Miliary Tuberculosis referred from Ojha Institute Of Chest Disease (OICD) to our department were included in the study. Detailed examination at the first visit was conducted and then after 2 months and 6 months. Complete examination including visual acuity, color vision, refraction, slit lamp examinations, intraocular pressure (IOP), and posterior segment evaluation after pupil dilatation was performed. Fundus photographs were also taken. Data was recorded and analyzed in SPSS version 16. Frequencies and percentages were calculated for age, gender and visual outcome. Results: Two hundred and seventy two (272) cases were included in the study. Age ranges from 10 to 80 years with mean age being 45 years. There were 140 (51.41%) female and 132 (48.53%) males. Among these two hundred and seventy two (272) cases, 14 (5.14%) had choroidal tubercles. They were all on anti tuberculous treatment. Visual acuity improved from less than 6/60 to 6/9 or 6/6 in majority of cases after completion of treatment and healing of choroidal tubercles was also noted. Conclusion: The study is unique and done for the first time in Pakistan. Frequency of choroidal tubercles with diagnosed cases of Miliary Tuberculosis is 5.14% with gender distribution female to male was 8:6. Visual outcome is better if the patient is screened early and treated promptly. Key Words: Choroidal Tubercles, Miliary Tuberculosis, Visual outcome